Phase stability of 3Y-TSZ ceramics after different surface treatments - Calambas Pulgarin, Heydy Lorena (2015)
The ability of zirconia ceramics to develop a bioactive surface is of great importance for biomedical applications. For that, it is also required to control phase stability (i.e. to avoid the tetragonal to monoclinic phase transformation) of zirconia surfaces in order to impart a high mechanical resistance. In this work, the phase stability of dense 3 mol% yttria stabilized-zirconia (3Y-TSZ) ceramics after acid and hydrothermal treatments was examined. Ceramic discs were prepared by slip casting from well dispersed 52 vol% suspensions, and subsequently sintered to 1300-1500 °C. The effect of various synthesis parameters and 0.25 wt% alumina doping on the phase transformation after acid and hydrothermal treatments was semi-quantitatively evaluated by XRD. The 3Y-TSZ sintered to 1500°C exhibited higher t→m transformation than samples sintered at lower temperatures. The phase transformation up to10h of hydrothermal treatment occurred by nucleation and growth mechanisms in which the nucleation process predominated. The presence of 0.25 wt% alumina in 3Y-TSZ sintered at 1500°C slightly enhanced the resistance to acid treatment.